Heated thin film gauge arrangements to reduce uncertainty in transient heat transfer measurements. (2nd November 2020) - Usandizaga, Inés; Beard, Paul; Chana, Kam; Povey, Thomas
Abstract: This paper describes the development of heated double-sided thin film gauge configurations for transient heat transfer measurements. By heating the substrate it is possible to measure the heat flux over a range of surface temperatures and deduce the adiabatic wall temperature and the external heat transfer coefficient. The accuracy of the measurement depends on the stability of the regression of heat flux against wall temperature and can be improved by extending the range of wall temperature over which the regression is performed. In this paper we compare two methods of local heating: double-sided gauges with an underside thin film heater and self-heating double-sided gauges. Both arrangements have been used in the Oxford Turbine Research Facility to measure the heat transfer on the uncooled turbine shroud of the MT1 high-pressure turbine stage at engine-representative conditions. These measurements yield improved regressions compared to conventional techniques to determine the adiabatic wall temperature and the heat transfer coefficient.